Positive and Negative Impacts of Poligamy in The Life of Muslim Family - Rohmadi Rohmadi; Fauzan Fauzan; Wahyu Abdul Jafar (Jurnal Madania)
This study aims to reveal in detail the positive and negative impacts that arise from polygamy in Muslim family life. This research is a literature review, which uses documentation techniques in finding the required data. While the analytical method used is the inductive method. After conducting in-depth research, conclusions are obtained, including: The positive impact of polygamy is the opening of a way out of emergency conditions that occur in the household. Polygamy can be a solution for people to avoid committing adultery/infidelity. Polygamy can also be a solution for someone to have children if his first wife is barren, protect widows, or channel the sexual needs of a husband who cannot be channeled properly with his first wife. While the negative impact that arises from polygamy for Muslim families is psychologically, a wife will feel disturbed and hurt to see her husband having sex with other women. A number of studies have shown that the average wife when she finds out her husband remarried spontaneously experiences feelings of depression, prolonged stress, sadness and disappointment. In addition, the relationship between husband and wife and their extended family is not harmonious. Marriage essentially connects the bond between two large families, polygamy makes the bond disrupted, maybe even broken. In addition, in the life of a polygamous family, of course, there are concerns in fostering and meeting family needs.